Korosi Retak Tegang pada Pipa Superheater Ketel Uap yang Baru Dibangun [Stress Corrosion Cracking of Cage Superheater Tubes of a Newly Built Boiler] - Adnyana, Dewa Nyoman (Jurnal Metalurgi, 2017)
A number of cage superheater tubes of a newly built steam boiler have been leaking during boiler’s first start-up commissioning. Leaking occurred when the boiler had just reached a pressure of 23.7 barg and temperature 4050 C from the intended operating pressure of 53 barg and temperature of 4850C. Type of failure and factors that may have caused the leakage of the cage superheater tube are discussed in this paper. The metallurgical assessment was conducted by preparing a number of specimens from the as received leaked cage superheater tube. Various laboratory examinations were performed including macroscopic examination, chemical composition analysis, metallographic examination, hardness test and SEM (scanning electron microscopy) examination equipped with EDS (energy dispersive spectroscopy) analysis. Results of the metallurgical assessment obtained show that the leaked cage superheater tubes have been experiencing stress-corrosion cracking (SCC) caused by the combined effect of corrosion and tensile stress. The corrosion agent that may have been responsible for the occurrence of SCC in the tube was mostly due to caustic sodium (Na) and other elements in a lesser extent such as Ca, Cl, S and P.